The determinants of international tourists arrival in Malaysia / Nurul Munirah Ahmad Fauzani - Ahmad Fauzani, Nurul Munirah (2016)
Tourism plays an extraordinary and growing role in global economy. It used to measure the economic condition of a country especially on international tourism visitor. The issue of tourism industry in Malaysia has pretty much been going down the drain. Some 27.4 million people visited Malaysia in 2014, but that number of tourist arrivals in Malaysia has seen a 30% drop in the last six months alone. The objective of this study to determine the factors that affecting international tourist’s arrival in Malaysia. Correlation and significant between gross domestic product (GDP), exchange rate (EXR), crime rate (CR), and financial crisis (FC) with international tourists arrival in Malaysia (ITA) are among the analysis. In this research, the data that used for the period 30 yearly starting 1986 until 2015 which is that had collect from Data Stream, World Bank, Department Statistics, Tourism Malaysia and Headquarter Police Station, Bukit Aman. This paper found that gross domestic product and financial crisis are determinant of international tourist arrivals in Malaysia (ITA); where they are significantly influence with ITA. However, exchange rate and crime rate did not significantly influence with ITA. From the results, gross domestic product and crime rate contribute positive relationship to the determinants of international tourist arrivals in Malaysia while exchange rate and financial crisis is negatively relationship with the determinants of international tourist arrivals in Malaysia. The most influencing towards the determinants of international tourist arrivals in Malaysia is the gross domestic product that signifies between ITA